Intercultural Sensitivity in Indonesian and Japanese Literary Works is the Development of Literary Learning in the Digital Era - Simanjuntak, Nensy Megawati; Wardhani, Widya Desary Setia; Sumartono, Sumartono; Padmasari, Arumtyas Puspitanig; Tobing, Victor MTL; Kumar, Atul (Vocational College of Diponegoro University, 2025)
Intercultural or another term for intercultural is a concept that brings together two or more cultural elements to then be integrated into new knowledge and understanding for each individual or group of people who want to know about the development of foreign cultures. In learning literature, intercultural is needed as a forum to develop global insight and knowledge. Learning literature is not only learning about the nature and content of literary works, learning literature means learning to be cultured and cultivating the culture itself. The data for this study were taken from famous novels from each country. The research data are: A novel entitled